Hot Branching Dynamics in a Light‐Harvesting Iron Carbene Complex Revealed by Ultrafast X‐ray Emission Spectroscopy. (31st October 2019) - Tatsuno, Hideyuki; Kjær, Kasper S.; Kunnus, Kristjan; Harlang, Tobias C. B.; Timm, Cornelia; Guo, Meiyuan; Chàbera, Pavel; Fredin, Lisa A.; Hartsock, Robert W.; Reinhard, Marco E.; Koroidov, Sergey; Li, Lin; et al.
Abstract: Iron N‐heterocyclic carbene (NHC) complexes have received a great deal of attention recently because of their growing potential as light sensitizers or photocatalysts. We present a sub‐ps X‐ray spectroscopy study of an Fe II NHC complex that identifies and quantifies the states involved in the deactivation cascade after light absorption. Excited molecules relax back to the ground state along two pathways: After population of a hot 3 MLCT state, from the initially excited 1 MLCT state, 30 % of the molecules undergo ultrafast (150 fs) relaxation to the 3 MC state, in competition with vibrational relaxation and cooling to the relaxed 3 MLCT state. The relaxed 3 MLCT state then decays much more slowly (7.6 ps) to the 3 MC state. The 3 MC state is rapidly (2.2 ps) deactivated to the ground state. The 5 MC state is not involved in the deactivation pathway. The ultrafast partial deactivation of the 3 MLCT state constitutes a loss channel from the point of view of photochemical efficiency and highlights the necessity to screen transition‐metal complexes for similar ultrafast decays to optimize photochemical performance. Abstract : Ein Eisen(II)‐NHC‐Komplex wurde durch Sub‐Pikosekunden‐Röntgenspektroskopie untersucht, um die Zustände, die an der Deaktivierungskaskade nach der Lichtabsorption beteiligt sind, zu identifizieren und zu quantifizieren. Nach der Besetzung eines angeregten 3 MLCT‐Zustands relaxieren 30 % der Moleküle ultraschnell in den 3 MC‐Zustand, parallel zu einem langsameren Pfad über den relaxierten 3 MLCT‐Zustand.